Efficacy of Sclerotherapic Agents in the Treatment of Simple Ovarian Cysts Created by Experimental Rat Model - Bakal, Unal; Sarac, Mehmet; Tartar, Tugay; Atilgan, Remzi; Kuloglu, Tuncay; Dagli, Adile Ferda; Kazez, Ahmet (Istanbul Training & Research Hospital, 2020)
Introduction: The purpose of this study is to investigate the effects of tetracycline (TC), clarithromycin (CM) and bleomycin (BLM) on the cyst diameter and ovarian tissues in the treatment of simple ovarian cysts. Methods: We employed Wistar albino female rats (n=38) to create ovarian cysts, and did not intervene in any form in the control group (GC) (n=6). In total, 32 female rats underwent unilateral salpingectomy for the creation of cysts. Macroscopic cysts were manifested in 25 (78%) rats who underwent salpingectomy. We divided the rats (n=25) with cysts into four groups. Salpingectomy with saline was performed in G1, salpingectomy with tetracycline (TC) was performed in G2, and salpingectomy with Clarithromycin (CM) was performed in G3. Additionally, salpingectomy with BLM was exploited in G4. Results: There was a significant decrease in the diameter of the cyst in G2 as compared to G1, but there was no significant difference among the other groups. There was no significant change in total ovarian reserve in the groups (p=0.066). There was a statistically significant increase in fibrosis in G1 and G3 groups as compared to GC (p<0.0001). As compared to G1, fibrosis was significantly decreased in G2 (p=0.003) and G4 (p=0.0001). TUNEL positivity was similar in GC and G1; however, there was a significant increase of TUNEL positivity in G2, G3 and G4 as compared to the control group (p<0.0001). In addition, there was a significant increase of adhesion in G2 (p=0.030) and G3 (p=0.010) as compared to G1. Conclusion: TC is a more effective agent than CM and BLM in the sclerotherapy treatment of ovarian cysts. These three agents have no negative effect on the total ovarian reserves. There is an increasing need for further clinical studies regarding the use of sclerotherapy agents, primarily concerning the TC, in the treatment of simple ovarian cysts.
Keywords: Ovarian cyst; sclerotherapy; tetracycline; clarithromycin; bleomycin